Associations of Mediterranean-style Diet Adherence with Circulating Sphingolipid Patterns (P18-004-19). (13th June 2019) - Bigornia, Sherman; Scott, Tammy; Barth, Brian; Ordovas, Jose M; Tucker, Katherine
Abstract: Objectives: Building evidence suggests that greater adherence to a Mediterranean-style diet (MD) may reduce the risk of cardiovascular disease, type 2 diabetes, and dementia. However, our understanding of the biological mechanisms explaining these associations is limited. Altered sphingolipid metabolism (e.g., increased ceramides, glycosyl- and lactosyl-ceramides, sphingoid bases, and sphingomyelin (SM)) has been implicated in the development of chronic health conditions. We aimed to quantify the impact of MD adherence on circulating patterns of sphingolipid metabolites. Methods: Cross-sectional analyses were conducted in the Boston Puerto Rican Health Study among those with available data ( n  = 540, 56 y, 74% women). Diet was obtained with a semi-quantitative FFQ. The MD score (MDS) includes 7 beneficial (e.g., fish, monounsaturated/saturated fat ratio (MUFA/SFA)) and 2 moderation components (e.g., meat and dairy) (range 0–9). Metabolomic analysis was conducted on plasma samples using ultra-high-performance liquid chromatography-tandem mass spectrometry. Twenty-six sphingolipids were retained for analyses. Principal components analysis was used to derive 5 sphingolipid patterns. Statistical analyses included multiple linear regression and ANCOVA. Results: Circulating sphingolipid patterns were characterized by dihydro-SMs and SM species with very-long chain fatty acid groups (Factor 1); glycosyl- and lactosyl-ceramides (Factor 2); ceramides (Factor 3); sphingoid bases, sphinganine-1-phosphate and sphingosine-1-phosphate (Factor 4); and SM species with a sphingadienine group (Factor 5). Each 1-point increase in the MDS was associated with lower Factor 3 z-score (β = −0.07 ± 0.03, P  = 0.01), as well as with lower Factor 5 z-score (−0.08 ± 0.02, P  = 0.001). We observed that individual MDS components including whole grains, fish, and the MUFA/SFA ratio were associated with the sphingolipid patterns (Table 1 ). Conclusions: Our results suggest that a Mediterranean-style diet and components of the diet may reduce circulating concentrations of ceramides and certain sphingomyelin species. This may in part explain the protective benefits of this dietary pattern. Longitudinal analyses are needed to clarify the long-term impact of this dietary pattern on sphingolipid metabolism. Funding Sources: NIH grants P01-AG023394 P50-HL105185 and R01-AG027087. Supporting Tables, Images and/or Graphs: